Leadership in Action: Out in the Open: How Team Leaders Can Deal with Sensitive Issues - Lindoerfer, Dennis (Center for Creative Leadership, 2007)
A wide range of sensitive issues can emerge in a team environment, and the range of causes can be equally wide. Such issues can threaten a team's viability and the quality of the final work product. Team leaders may need to intervene when such situations develop, and once they have decided to intervene, they need to know how best to do so.